Subjective resilience among women and youth clients of social innovation projects executed in five regions of Ethiopia - Dejene, Melisew; Yimer, Semeredin; Fentaw, Tenaw; Regassa, Nigatu (Frontiers in Sustainable Food Systems, 2024)
The European Union (EU) launched an EU-RESET Plus Innovation Fund in Ethiopia, with a goal of building the resilience and improving the livelihood of targeted vulnerable communities in five regions. The respective social innovation projects (SIPs) introduced social innovations that part with the ‘business-as-usual’ model. Though difficult to study impact due to the limitations of cross-sectional survey design adopted, the study aimed to investigate the level of subjective resilience exhibited by women and youth clients and the predictors of resilience. We collected quantitative data from 910 client households. We also conducted over a dozen case story interviews with project clients. We employed World Food Program (WFP) (2022) subjective resilience score to compute clients’ level of subjective resilience. An ordered logistic regression with subjective resilience as an outcome variable was conducted to determine predictors. The unique contribution of this study is the computation of the subjective resilience of project beneficiaries in objective terms, having three categories. The findings revealed that the SIPs contributed to boosting the resilience of women and youth, with significant predictors including active involvement, empowerment, gender, savings, and livestock ownership. Gender differentials are also found to be for future development projects to consider in their design and practice.